Evaluation of Tillage, At-Planting Treatment, and Nematicide on Tobacco Thrips (Thysanoptera: Thripidae) and Reniform Nematode (Tylenchida: Hoplolamidae) Management in Cotton - Whitney D. Crow; Angus L. Catchot; Jeff Gore; Darrin M. Dodds; Donald R. Cook; Thomas W. Allen (Agronomy, 2020)
There are numerous early-season pests of cotton, Gossypium hirsutum L., that are economically important, including tobacco thrips, Frankliniella fusca (Hinds), and reniform nematode, Rotylenchulus reniformis (Linford & Oliveira). Both of these species have the potential to reduce plant growth and delay crop maturity, ultimately resulting in reduced yields. A field study was conducted during 2015 and 2016 to evaluate the influence of tillage, at-planting insecticide treatment, and nematicide treatment on pest management, cotton development, and yield. Treatment factors consisted of two levels of tillage (no-tillage and conventional tillage); seven levels of at-planting insecticide treatments (imidacloprid, imidacloprid plus thiodicarb, thiamethoxam, thiamethoxam plus abamectin, acephate plus terbufos, aldicarb, and an untreated control); and two levels of nematicide (no nematicide and 1,3-dichloropropene). There were no significant interactions between tillage, at-planting insecticide treatment, or nematicide for any parameters nor was there a difference in the main effect of nematicide on thrips control or damage. The main effects of tillage and at-planting insecticide treatment impacted thrips densities and damage. The no-tillage treatments and aldicarb in-furrow or acephate seed treatment plus terbufos in-furrow significantly reduced thrips populations. Early-season plant response was impacted by tillage and at-planting insecticide treatment; however, that did not result in significant yield differences. In regard to nematicide treatment, the use of 1,3-dichloropropene resulted in lower yields than the untreated.